An examination of adolescent athletes and nonathletes on baseline neuropsychological test scores - Tomczyk, C. P.; Mormile, M.; Wittenberg, M. S.; Langdon, J. L.; Hunt, T. N. (Journal of Athletic Training, 2018)
Context: An estimated 15.3 million adolescent students are enrolled in US high schools, with approximately 7.8 million participating in athletics. Researchers have examined various demographics in high school athletes; however, athletic participation may play a larger role in test performance than previously thought. Currently, investigations of concussion assessment may rely on uninjured athletes as controls. However, due to the intense nature of athletics, this may not be an appropriate practice.